Persistent Immune Activation in Human Immunodeficiency Virus–Infected Pregnant Women Starting Combination Antiretroviral Therapy After Conception. (29th March 2021) - Lohman-Payne, Barbara; Koster, Jacob; Gabriel, Benjamin; Chilengi, Roma; Forman, Leah S; Heeren, Tim; Duffy, Cassandra R; Herlihy, Julie; Crimaldi, Steven; Gill, Chris; Chavuma, Roy; Mwananyanda, Lawrence; et al.
Abstract: This study evaluated the impact of human immunodeficiency virus (HIV) and combination antiretroviral therapy (cART) on immune activation during pregnancy in a Zambian cohort of HIV-exposed but uninfected children followed up from birth. Activated CD8 + T cells (CD38 + and HLA-DR + ) were compared among HIV-uninfected (n = 95), cART experienced HIV-infected (n = 111), and cART-naive HIV-infected (n = 21) pregnant women. Immune activation was highest among HIV-infected/cART-naive women but decreased during pregnancy. Immune activation HIV-infected women who started cART during pregnancy was reduced but not to levels similar to those in HIV-uninfected women. The effects of elevated maternal immune activation in pregnancy on subsequent infant health and immunity remain to be determined. Abstract : Human immunodeficiency virus (HIV)–infected women who started combination antiretroviral therapy (cART) during pregnancy experienced reduced T-cell immune activation but not to levels similar to those in pregnant cART-experienced HIV-infected or HIV-uninfected women. The effect of maternal immune activation during early life on infant immunity remains undefined.